Effects of plant growth-promoting rhizobacteria on co-inoculation with Bradyrhizobium in soybean crop: a meta-analysis of studies from 1987 to 2018 - Douglas M. Zeffa; Lucas H. Fantin; Alessandra Koltun; André L.M. de Oliveira; Maria P.B.A. Nunes; Marcelo G. Canteri; Leandro S.A. Gonçalves (PeerJ, 2020)
Background The co-inoculation of soybean with Bradyrhizobium and other plant growth-promoting rhizobacteria (PGPR) is considered a promising technology. However, there has been little quantitative analysis of the effects of this technique on yield variables. In this context, the present study aiming to provide a quantification of the effects of the co-inoculation of Bradyrhizobium and PGPR on the soybean crop using a meta-analysis approach. Methods A total of 42 published articles were examined, all of which considered the effects of co-inoculation of PGPR and Bradyrhizobium on the number of nodules, nodule biomass, root biomass, shoot biomass, shoot nitrogen content, and grain yield of soybean. We also determined whether the genus of the PGPR used as co-inoculant, as well as the experimental conditions, altered the effect size of the PGPR. Results The co-inoculation technology resulted in a significant increase in nodule number (11.40%), nodule biomass (6.47%), root biomass (12.84%), and shoot biomass (6.53%). Despite these positive results, no significant increase was observed in shoot nitrogen content and grain yield. The response of the co-inoculation varied according to the PGPR genus used as co-inoculant, as well as with the experimental conditions. In general, the genera Azospirillum, Bacillus, and Pseudomonas were more effective than Serratia. Overall, the observed increments were more pronounced under pot than that of field conditions. Collectively, this study summarize that co-inoculation improves plant development and increases nodulation, which may be important in overcoming nutritional limitations and potential stresses during the plant growth cycle, even though significant increases in grain yield have not been evidenced by this data meta-analysis.